Mode Choice Modelling For Work Trips in Calicut City - Tushara T, Rajalakshmi P and Bino I Koshy (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2013)
Transportation modelling plays an important role in supporting transportation planning. Work trips are centre of focus of urban transportation planning and policy analysis. This may causes congestion in peak hours in the urban transportation network. One of the important aspects of transportation modelling is to predict the travel choice behaviour. The travel choice behaviour is also referred to as traveller mode choice, which is the most frequently modelled travel decision. It involves a specific aspect of human behaviour dedicated to choice decisions. With a model, as simplified representation of a part of reality provides a better understanding and interpreting of these complex systems. This paper investigates mode choice behaviour of employers in Calicut city. A multinomial logit model (MNL) with statistical data processing software SPSS was used for explaining travel patterns and mode choice of employees residing in Calicut city. MNL model was developed and identified the factors influencing the mode choice of work trips.MNL is widely used model in the discrete choice model and it has many computational advantages.